A prospective blinded comparison of second trimester fetal measurements by expert and novice readers using low-cost novice-acquired 3D volumetric ultrasound. (3rd June 2021) - Salinaro, Julia R.; McNally, Patricia J.; Nickenig Vissoci, Joao R.; Ellestad, Sarah C.; Nelson, Brian; Broder, Joshua S.
Abstract: Rationale and objectives: Two-dimensional (2D) ultrasound (US) is operator dependent, requiring operator skill and experience to selectively identify and record planes of interest for subsequent interpretation. This limits the utility of US in settings in which expert sonographers are unavailable. Three-dimensional (3D) US acquisition of an anatomic target, which enables reconstruction of any plane through the acquired volume, might reduce operator dependence by providing any desired image plane for interpretation, without identification of target planes of interest at the time of acquisition. We applied a low-cost 3DUS technology because of the wider potential application compared with dedicated 3DUS systems. We chose second trimester fetal biometric parameters for study because of their importance in maternal-fetal health globally. We hypothesized that expert and novice interpretations of novice-acquired 3D volumes would not differ from each other nor from expert measurements of expert-acquired 2D images, the clinical reference standard. Materials and methods: This was a prospective, blinded, observational study. Expert sonographers blinded to 3DUS volumes acquired 2DUS images of second trimester fetuses from 32 subjects, and expert readers performed interpretation, during usual care. A novice sonographer blinded to other clinical data acquired oriented 3DUS image volumes of the same subjects on the same date. Expert readers blinded to other data assessed placental location (PL), fetal presentation (FP), and amniotic fluid volume (AFV) in novice-acquired 3D volumes. Novice and expert raters blinded to other data independently measured biparietal diameter (BPD), humerus length (HL), and femur length (FL) for each fetus from novice-acquired 3D volumes. Corresponding gestational age (GA) estimates were calculated. Inter-rater reliability of measurements and GAs (expert 3D versus expert 2D, novice 3D versus expert 2D, and expert 3D versus novice 3D) were assessed by intraclass correlation coefficient (ICC). Mean inter-rater measurement differences were analyzed using one-way ANOVA. Results: 3D volume acquisition and reconstruction required mean 30.4 s (±5.7) and 70.0 s (±24.0), respectively. PL, FP, and AFV were evaluated from volumes for all subjects; mean time for evaluation was 16 s (±0.0). PL, FP, and AFV could be evaluated for all subjects. At least one biometric measurement was possible for 31 subjects (97%). Agreement between rater pairs for a composite of all measures was excellent (ICCs ≥ 0.95), and for individual measures was good to excellent (ICCs ≥ 0.75). Inter-rater differences were not significant ( p  > .05). Conclusions: Expert and novice interpretations of novice-acquired 3DUS volumes of second trimester fetuses provided reliable biometric measures compared with expert interpretation of expert-acquired 2DUS images. 3DUS volume acquisition with a low-cost system may reduce operator dependence of ultrasound.